The use of wearable pulse oximeters in the prompt detection of hypoxemia and during movement: diagnostic accuracy study - Santos, M; Vollam, S; Pimentel, M; Morgado Areia, C; Young, L; Roman, C; Ede, J; Piper, P; King, E; Harford, M; Shah, A; Gustafson, O; et al. (JMIR Publications, 2022)
Background: Commercially available wearable (ambulatory) pulse oximeters have been recommended as a method for managing patients at risk of physiological deterioration, such as active patients with COVID-19 disease receiving care in hospital isolation rooms; however, their reliability in usual hospital settings is not known.